PERLINDUNGAN ANAK DARI TINDAK PIDANA ATAS PERILAKU YANG BERKONFLIK DENGAN HUKUM - Ibnu Fajar Fri (Institut Agama Islam Negeri Metro, 2021)
Not a few children have problems with the law or in conflict with the law. The formulation of juvenile delinquency as a criminal offense, suppose it is committed on adult crimes but in adults it is called Juveline Delinquency. The principle of justice for children with problems / conflicts with legal guarantees and genuine and optimal services provided to children in legal and judicial processes. The issues discussed in this journal include legal protection and restrictions on children who are in trouble with the law or in conflict with the law. Then it is not school children who get justice in article 28 B paragraph 2 of the 1945 NRI Law which is the basis based on child protection in Indonesia. The research was conducted using the normative legal method which relies on the Law and Conceptual approach. Furthermore, the results of the study do not guarantee legal uncertainty caused by disharmony in the understanding of children. And the regulation of legal protection for children who have problems with the law or conflict with the law, both in special treatment in procedural law, the threat of punishment is different from that of adults, the fulfillment or realization of child judges and prioritizing justice is contained in Law No. 23 of 2002 concerning Child Protection which it becomes Law No. 35 of 2014 and Law No. 11 of 2012 related to the Juvenile Criminal Justice System.